1997
DOI: 10.1111/j.1469-7610.1997.tb01694.x
|View full text |Cite
|
Sign up to set email alerts
|

A Family Study of Autism: Cognitive Patterns and Levels in Parents and Siblings

Abstract: First-degree relatives of 99 autism probands and of 36 Down's syndrome controls were assessed with standardised tests of intellectual functioning, reading, and spelling. Higher mean verbal IQ scores, and discrepancies in favour of verbal scores, were characteristic of autism relatives. No consistent differences were found on performance scales, reading, and spelling tests. Among autism relatives, siblings affected with the broad phenotype of autism had significantly lower IQ scores and poorer reading and spell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
5
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 36 publications
10
148
5
5
Order By: Relevance
“…Results on the Block Design Test showed no significant difference in performance, neither when groups were compared as a whole nor when fathers and mothers were compared separately. Earlier studies found the same results (Fombonne et al, 1997;. One could therefore say that the Block Design Test is not sensitive enough to detect subtle differences in central coherence.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Results on the Block Design Test showed no significant difference in performance, neither when groups were compared as a whole nor when fathers and mothers were compared separately. Earlier studies found the same results (Fombonne et al, 1997;. One could therefore say that the Block Design Test is not sensitive enough to detect subtle differences in central coherence.…”
Section: Discussionmentioning
confidence: 56%
“…Although some studies did not find parents with an autistic child do better on the Block Design Test (Fombonne, Bolton, Prior, Jordan, & Rutter, 1997; found fathers with an autistic child to do notably better on the Block Design Test than fathers with dyslexic children or normally developed children. No significant difference was found between the groups of mothers.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies of the parents of children with ASDs a cognitive impairment could not be established. [12][13][14][15][16] An understanding of the extent to which autistic traits and IQ share genetic and environmental factors is important for classifying ASDs as well as for locating and identifying genes that contribute to ASDs. Surprisingly, there is no other published study on twins that assesses the relationship between autistic traits and IQ.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported problems in early language development by relatives of ASD probands have been noted in several studies (Bolton et al, 1994;Folstein et al, 1999;Fombonne et al, 1997;Szatmari et al, 2000). Evidence of language deficits with direct testing, however, is less reliable.…”
Section: Heritability Of Language Impairment In Asdmentioning
confidence: 99%